O Trabalho e o labirinto da responsabilidade socioempresarial:a experiência da cidadania empresarial do Banco do Brasil - Ponte, Júlio Ramon Teles da (2011)
In the current systemic crisis, economic policy is directed to correct the consequences of the functioning of this metabolism, but within the limits of the capital. From this perspective, decision makers propose trade policies, agricultural and industrial to ensure conditions for economic growth. However, as a dead end, there is failure of the State in giving efficacy to the operation of all segments of the economy, especially given the budget constraint. Public managers are forced to seek external resources, resuming the cycle of political allegiance to the interests of international financial and banking representatives, installed in so-called multilateral. The complex ideological capital comes into play in trying to convince society that the paths taken by governments are inevitable, and that capitalism can be "humanized", even with the realization of the growing inequalities caused by historical irrationalism of the production process of capital . In this sense, emerging concepts that attempt to demonstrate the compatibility of the system to real human needs. This ideological offensive is intended to legitimize the capital. The so-called third sector has a special highlight with the concept of corporate social responsibility. It creates a political environment in which the inevitable mix-up with new illusions offered by and often funding the metabolism of capital in order to perpetuate this system. In this context, political elites, and considerable portions of the academy, embark on "waves of capitalist optimism," while the sociometabolismo capital expands its historical limits, driving forces postponing their collapse, but that cause human suffering and ecological stress. Wars are disseminated to strengthen the deadly war industry and the automobile industry; and devastating the environment of which depends the capital system. In this scenario disassemble, propositions emerge around a "new social pact" in order to minimize the adverse effects of the dynamics of reproduction of capital. The business class is called to exercise its role through the discourse that appeals to social responsibility programs, in order to intervene directly in the "social question". The core of this research is precisely this point. Although there is considerable scholarship on the phenomenon of Social Responsibility and Corporate Citizenship, there is also an evident lack of this approach focused on the banking sector in Brazil. The importance of rentier capital increased ownership of shares in the wealth produced by all of Brazilian society, justifies a sociological research project on Social Responsibility in the domestic financial sector. In this sense, it was decided to perform a dynamic approach to the "Corporate Citizenship" in the banking industry, specifically in the Bank of Brazil. As this is a key institution, is important analyze of the impacts of this strategy fetish of capitalist reproduction, in order to evaluate the social legitimization of rentier capital in Brazil. In this scenario of the abundance of the discourse on social responsibility there exist a progressive impoverishment of professional work in this segment in Brazil. There is a dramatic mismatch between rhetoric and practice because of the trend of deepening vulnerability of the working conditions of the Brazilian bank worker, from the 1990's. In the specific case of the Bank of Brazil, the first initiative of the institution was to conform to the principles of the UNO and the Ethos Institute, aiming to align their domestic policies to this new strategy of domination of capital. The purpose is to place the Bank in the ideological sphere of corporate social responsibility, just as with its partners in the private financial intercapitalist competition. Indeed, in the internal ambit of the Bank of Brazil, there is a policy to adjust its functional segments to the doctrine of Social Corporate Responsibility. The concepts of this doctrine is presented as something inexorable. There are no alternatives. The Bank of Brazil operates in a highly competitive market, the segment featuring the dominance of financial capital accumulation today. For this reason it can not fail to incorporate the technological advances organizational. For employees there is no alternative but to adapt to this new set of ideas proposed by the metabolism of capital